2017
DOI: 10.1016/j.biopsych.2016.03.2104
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Specific Dopamine Abnormalities in Schizophrenia

Abstract: In light of the clinical evidence implicating dopamine in schizophrenia, and the prominent hypotheses put forth regarding alterations in dopaminergic transmission in this disease, molecular imaging has been used to examine multiple aspects of the dopaminergic system. Here we review the imaging methods used and compare the findings across the different molecular targets. Findings have converged to suggest early dysregulation in the striatum, especially in the rostral caudate, manifesting as excess synthesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
210
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(227 citation statements)
references
References 129 publications
14
210
1
2
Order By: Relevance
“…Our findings suggest that Arc function is important for establishing the proper activity balance between mesocortical and mesostriatal dopaminergic circuits. Moreover, our studies further suggest that these circuit deficits can arise together from the same genetic background, which has been difficult to determine in humans due to different dopamine molecular imaging methods in striatal and cortical regions and genetic diversity (Weinstein et al, 2016). …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our findings suggest that Arc function is important for establishing the proper activity balance between mesocortical and mesostriatal dopaminergic circuits. Moreover, our studies further suggest that these circuit deficits can arise together from the same genetic background, which has been difficult to determine in humans due to different dopamine molecular imaging methods in striatal and cortical regions and genetic diversity (Weinstein et al, 2016). …”
Section: Discussionmentioning
confidence: 93%
“…To investigate how Arc genetic mutations might affect the dopaminergic system, we first analyzed Arc mutants for dopamine content in PFC and striatum, two major areas involved in the dopamine hypothesis of schizophrenia (Koch et al, 2014, Simpson et al, 2010, Weinstein et al, 2016, Winterer and Weinberger, 2004). In the PFC, an Arc effect was present on dopamine tissue content (F 2,71 =6.72, p=0.002, Figure 4A), but not on noradrenaline (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Both VS and AS have been indirectly implicated in generating the psychotic symptoms. Four studies have identified higher dopamine activity in the AS relative to SMS in patients with SZ (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The DBS clinical trials to date have been funded through grants (NCT0237505 and NCT01725334), and by seeking FDA, IDE along with Centers for Medicare and Medicaid Services approval for reimbursement (NCT02361554). 48 …”
Section: Methodsmentioning
confidence: 99%